(untitled) (Psychology Travelogs, 2024)
In the article, an analysis of the results of a study on the peculiarities of emotional intelligence development in future specialists of socio-economic profile is presented, particularly in future psychologists, social workers, and physical education and sports teachers. This issue becomes especially relevant in the conditions of constant changes in Ukrainian society and technological development, which require future professionals to be more competent in interpersonal relationships, effective communication, conflict resolution, and decision-making based on emotional intelligence. It has been proven that numerous studies and articles dedicated to emotional intelligence have primarily focused on identifying it as a personal trait, but only a limited number of scholars have explored emotional intelligence as a key professional quality. In the current professional environment, where not only technical but also social competence is demanded, self-awareness of one’s emotions becomes a crucial skill. Mastering empathy skills and understanding the emotions of others is identified as one of the most crucial components of emotional intelligence for professionals in the modern professional setting. It is argued that a high level of emotional intelligence contributes to the development of empathy and understanding of others’ emotions, serving as the foundation for harmonizing emotions and intellect, experiencing inner freedom and responsibility to oneself, recognizing personal needs and motives, maintaining emotional balance, and adjusting life strategies. Diagnostic results have provided integrative indicators of emotional intelligence development and levels of expression of its individual components. A tendency towards improvement in the level of emotional intelligence development among students in their graduating year compared to the initial stage has been identified, which may be associated with professional growth and a deeper understanding of emotional aspects in a socio-economic context. It has been clarified that there are certain aspects of emotional intelligence that are less developed in students of socio-economic profile, specifically in stress management, self-emotion management, and recognizing the emotions of others.